Approaches to determining the cost of laboratory tests - I. I. Khayrullin; V. V. Omelyanovskiy; R. V. Gostishchev; O. A. Sukhorukikh; S. A. Kovaleva; B. G. Gorodetsky (Фармакоэкономика)
Background. Determining the cost of laboratory tests is a significant factor in the context of economic analysis and management of clinical diagnostic laboratories. Information about costs allows medical organizations to plan operational activities more efficiently, optimize resource utilization, and exercise control over expenditures. These measures are aimed at improving the financial position and enhancing the operational efficiency of the laboratories.Objective: to review various methods for calculating the cost of laboratory tests.Material and methods. The study included the collection and analysis of publications on calculating cost of laboratory tests, determining their prime cost in PubMed/MEDLINE and Google Scholar databases, as well as in Google and Yandex search engines for similar “cost laboratory test” query. The regulatory documents of the Russian Federation in this area were considered.Results. For calculating the prime cost of laboratory tests such methods as direct costing, regulatory prime costing, total prime costing, activity-based costing (ABC), standard costing, costing for base service, department costing, cost-volume analysis are used. The ABC and standard cost methods provide the most accurate assessment of the impact of various factors.Conclusion. The approaches established by regulatory documents do not contradict each other and represent the implementation of total costing method. At the same time, a medical organization may use other methods for calculating the cost of laboratory tests, depending on the objectives of the analysis, the specifics of the laboratory and the cost accounting method adopted in accounting policy, the management accounting system.